Advancing Agribusiness through Systemic Approach: Linking Sectors, Resources, and Market Channels - Caraecle, Lovely Rose; Bandera , Abdani (Journal of Business Economics and Agribusiness, 2025)
Agribusiness is a key driver of economic growth, food security, and rural livelihoods in developing countries, particularly in Southeast Asia and the Philippines, where it employs a significant portion of the labor force and supports domestic consumption, trade, and value chains. Traditional agricultural practices, however, face challenges in addressing globalization, climate variability, and inclusive economic growth. This study employs a qualitative, literature-based approach, synthesizing over forty peer-reviewed articles, policy reports, and institutional publications from FAO, IFPRI, the World Bank, ADB, ASEAN, and SEARCA, to examine how a systemic framework—integrating sectoral linkages, resource mobilization, and market channels—can enhance agribusiness performance and sustainability. Findings highlight five critical dimensions: (1) sectoral linkages and integration, emphasizing horizontal and vertical networks that improve efficiency, resilience, and value creation; (2) resource mobilization and management, including sustainable natural resource use, financial inclusion, human capital development, and technological innovation; (3) market channel integration, encompassing formal and informal networks, digital platforms, and regional trade; (4) institutional and policy frameworks, with multi-stakeholder governance, regulatory alignment, and public-private partnerships; and (5) regional dynamics, showing varying system maturity across Southeast Asia. Comparative analysis indicates that Thailand and Vietnam demonstrate integrated, competitive agribusiness systems, while the Philippines remains fragmented. The study concludes that systemic approaches provide evidence-based strategies for building resilient, inclusive, and competitive agribusiness sectors, offering actionable recommendations for policymakers and stakeholders.